(3GdBjGJ GdYXjeI GdHGgQI aj eYQGL SjO Cgd GdOfjG hGdBNQIs - (3TeS GdOjf CHh YHO Gddg eMeO Hf jhSa Hf Ydj GdOeTbj GdUGdMj, TeS GdOjf GdTGej,J (B942 (3g` s ((3eMeO Hf eMeO eMH GdOjf Hf CMeO GdJfjSi GdeGdci s)
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY SjO Ndbg eMeO Edi CYdi ebGeGJ GdSYGOI hCSQi Hg djdG ef GdeSLO GdMQGe Edi GdeSLO GdCbUi eYOf GdCfHjGA GdCLdI GdbGOI s
(3BNQgG (B:s
(3hGdCTHg eG PcQfGg gfG Cf GdBaI ef ZjQ ejSQI hGddg CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi dhMI GdYfhGf Jedc heWGdYIs
(3ai BNQ GdfSNI ELGRI ehbYI HNW GdeDda s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdJGQjNs